Implementasi Sistem Monitoring Kualitas Air Pada Budidaya Tambak Udang Dan Bandeng - Ahmad Fatchi Machzar; Sabriansyah Rizqika Akbar; Hurriyatul Fitriyah (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
In 2006 there was a catastrophic mudflow disaster, which is currently still spraying mud and its impact is on the ponds around the mud that the mud is dumped into the river, the river water is the air circulation in the pond, thus the authors make tools for monitoring and implementation of real time automation system on the cultivation of shrimp ponds and milkfish, using pH sensors, temperature sensors, and turbidity sensor, The need to maintain the quality of pond water is good then the fish will be healthy, with very good results to consumers and farmers ponds. By including all sensors, including pH sensor, turbidity sensor and temperature sensor, after it is updated through Arduino Nano microcontroller and all these sensors on the Lcd that is in the system body. Automatic feeder using DC motors, by setting the timing on potentios, is ready to give the motor current time and the duration of the motor will rotate, from the potentialo input to the relay as the switch of the driving and motor commands. The result of this system test shows that the system gives the result of the sensor, the pH sensor gives the result if the acid solution of air is higher then the pH sensor will decrease, after which turbidity sensor gives the result if the more turbid the air sensor will be higher turbidity, and the result of temperature sensor , the higher the temperature of the air the higher the temperature sensor on the Lcd. For automatic feeding system that is motorcycle matrix will move and the duration of rotation of motor according to the input motor given at potentio.